HUBUNGAN PENGETAHUAN TENTANG KANKER SERVIKS DENGAN PERILAKU PEMERIKSAAN PAP SMEAR PADA WANITA USIA ANTARA 30 â 45 TAHUN - Nugroho, Christianto (Jurnal AKP, 2011)
Cervical cancer is a malignant process that occurs in the cervix, so that its surrounding tissue can not perform the function properly. Pap Smear is a method of examination of cells taken from the cervix and then examined under a microscope to see the changes that occur from such cells. Pap Smear Behaviour can be influenced by several factors such as, knowledge. Based on research results in sub-village Bulurejo RW 1 RT 1, 2, 3, 4, 5. from the total respondents who researched, data obtained the majority of respondents have good knowledge about cervical cancer but only a small proportion that checked of Pap Smear is fine. The purpose of this study was to examine the relationship between knowledge about the behavior of Cervical Cancer by Pap Smear in women aged between 30-45 years in Village of Bulurejo village of Kawedusan district of Plosoklaten, Kediri regency.Research design used Cross sectional that is a study that emphasizes the time of measurement / observation data dependent and independent variables only once at a time, the population in this study are women aged between 30-45 years in the sub village of Bulurejo RW 1 RT 1, 2, 3, 4, 5 Village of Kawedusan, district of Plosoklaten, Kediri regency (P value 0.018 <0.005 (α)) (Ho rejected). Relations between the two variables is positive and low (correlation coefficient 0.333) its mean the better knowledge about Cervical Cancer so the better of the examination behavior of Pap Smear.Results of research showed that most respondents have knowledge about Cervical Cancer in good categories amount to 29 respondents (45.31%) and only 6 respondents (9.37%) had a examination of Pap Smear behavior of a total 64 respondents.Results of research are that there is a relationship between knowledge of cervical cancer with Pap smear behavior so that knowledge about cervical cancer and Pap smear tests need to be improved. But there are some respondents with good knowledge level but does not perform Pap smears well. This can be influenced by several factors, including the factors of culture, beliefs and also the resources (facilities, money, time, and energy)